Mother Teresa : missionary of charity - Wellman, Sam. (Philadelphia, PA : Chelsea House Publishers, 1999)
Presents the life and times of the nun who founded the Order of the Missionaries of Charity in Calcutta, won the Nobel Peace Prize, and dedicated her life to helping the destitute.
Includes bibliographical references (p. 203-204) and index.
Christian Library.
6.0
5-8.
5-8
Keywords: Teresa, -- Mother, -- 1910- -- Juvenile literature; Teresa, -- Mother, -- 1910-; Teresa, -- Mother, -- 1910-; Missionaries of Charity -- Biography -- Juvenile literature; Missionaries of Charity; Missionaries of Charity -- Biography; Nuns -- India -- Calcutta -- Biography -- Juvenile literature; Missionaries; Nuns; Women -- Biography; Missionaries -- Biography; Nuns -- Biography; Women -- Biography